EEG brain oscillations are modulated by interoception in response to a synchronized motor vs. cognitive task - Angioletti, Laura; Balconi, Michela (Frontiers in Neuroanatomy, 2022)
So far, little is known about how conscious attention to internal body signals, namely, interoception, affects the synchronization with another person, a necessary or required social process that promotes affiliations and cooperation during daily joint social interactions. The effect of explicit Interoceptive Attentiveness (IA) modulation, conceived as the focus on the breath for a given time interval, on electrophysiological (EEG) correlates during an interpersonal motor compared to a cognitive synchronization task was investigated in this study. A total of 28 healthy participants performed a motor and a cognitive synchronization task during the focus and no-focus on the breath conditions. During the tasks, frequency bands (delta, theta, alpha, and beta band) from the frontal, temporo-central, and parieto-occipital regions of interest (ROIs) were acquired. According to the results, significantly higher delta and theta power was found in the focus condition in the frontal ROI during the execution of the motor compared to the cognitive synchronization task. Moreover, in the same experimental condition, delta and beta band power increased in the temporo-central ROI. The current study suggested two main patterns of frequency bands modulation during the execution of a motor compared to cognitive synchronization task while a person is focusing the attention on his breath. This study can be considered as the first attempt to classify the different effects of interoceptive manipulation on motor and cognitive synchronization tasks using neurophysiological measures.